Optimization of asymmetric bioreduction conditions of 1-(thiophen-2-yl)ethanone by Weissella cibaria N9 using a desirability function-embedded face-centered optimization model - Bolubaid, Mohammed; Ozdemir, Akin; Dertli, Enes; Alamoudi, Mohammed; Taylan, Osman; Karaboga, Dervis; Yilmaz, Mustafa Tahsin; Sahin, Engin (TAYLOR & FRANCIS INC, 2023)
Prochiral ketones can be effectively bio-reduced to chiral secondary alcohols by whole-cell biocatalysts, which are possible useful precursors to synthesize physiologically active chemicals and natural products. When whole-cell biocatalysts strains are used, bioreduction process can be influenced by various cultural factors, and it is vital to optimize these factors that affect selectivity, conversion rate, and yield. In this study, Weissella cibaria N9 was used as whole-cell biocatalyst for bioreduction of 1-(thiophen-2-yl)ethanone, and cultural design factors were optimized using a desirability function-embedded face-centered optimization model. For this, effects of pH (4.5-5.5-6.5, x(1)), (2) temperature (25-30-35 degrees C, x(2)), (3) incubation period (24-48-72 h, x(3)), and (4) agitation speed (100-150-200 rpm, x(4)) on two response variables; (1) ee (%) and (2) cr (%) were tested. Next, desirability function-embedded face-centered optimization model revealed that a pH of 6.43, a temperature of 26.04 degrees C, an incubation period of 52.41 h, and an agitation speed of 150 rpm were the optimum levels and the estimated ee and cr responses were 99.31% and 98.16%, respectively. Importantly, the actual experimental ee and cr responses were similar to the estimated values indicating the capability of the offered desirability function-embedded face-centered optimization model when using the optimum cultural conditions.
Keywords: Desirability function-embedded face-centered optimization; bioreduction; (S)-1-(thiophen-2-yl)ethanol; Whole-cell biocatalysts; Weissella cibaria N9; ENANTIOSELECTIVE REDUCTION; POLYMETHYLHYDROSILOXANE; HYDROGENATION; BIOCATALYSTS; CATALYSIS; KETONES; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology